Three-dimensional reconstruction of anomalous chloroplasts in transgenic ipt tobacco - Synková, Helena; Schnablová, Renáta; Polanská, Lenka; Husák, Michal; Siffel, Pavel; Vácha, Frantisek; Malbeck, Jirí; Machácková, Ivana; Nebesárová, Jana (Planta, 2006)
Anomalies in the ultrastructure of chloroplasts, from transgenic ipt tobacco, overproducing endogenous cytokinins (CKs) were studied. Detailed analyses of CKs and their metabolites showed that Pssu-ipt tobacco contained enhanced contents of CKs both in leaves and in isolated chloroplasts. The role of CKs in the formation of anomalous structures is suggested. Pssu-ipt chloroplasts frequently formed the distinct peripheral reticulum with a system of caverns that often involved mitochondria and/or peroxisomes. Large crystalloids, which were found in chloroplasts of Pssu-ipt, occupied up to 16% of chloroplast volume. We suggested that the crystalloids were formed by LHC II aggregates. This was supported by analysis of the fluorescence emission spectra at 77 degrees K, chlorophyll a/b ratio, immunogold staining of the structures, and crystallographic unit size analysis.
Keywords: regulace genové exprese u rostlin; geneticky modifikované rostliny; cytokininy; transgeny; Alkyl and Aryl Transferases; Genes, Plant; Plants, Genetically Modified; rostlinné geny; Chloroplasts; Nicotiana; Transgenes; Gene Expression Regulation, Plant; tabák; chloroplasty; alkyltransferasy a aryltransferasy; Cytokinins